Measuring The Level of Risk Maturity in Hospital using Risk Maturity Index (RMI) - Latumenasse, Arnetha Irene; Diyanty, Vera (E-Jurnal Akuntansi, 2026)
This study measure the level of risk management implementation at ABC Hospital using the Risk Maturity Indeks (RMI) that has already been adjusted with the Decree of the Minister of Health (Kepmenkes) No. 1596 of 2024 for the hospital context. The study was conducted in a class D private hospital beds, using a case study approach. To achieve the objective, we conduct the documentations study and semi-structured interviews with 6 respondents. The results indicate that ABC Hospital's risk maturity level remains in the Initial Phase (+), with an RMI score of 1.5. This suggest that formal risk management activities are conducted on an ad hoc basis to fulfill accreditation requirements, and still rely on Quality Committee.